Technology adaptation to climate change in level producers rice in West Java - Firda Liesdiana; Ni Putu Sekar Trisnaning Laksemi; Rizqy Fachria; Salma Nursaadah; Yanyan Ahmad Hoesen; Zamzam I'lanul A.A.; Yooce Yustiana (School of Life Sciences and Technology, Institut Teknologi Bandung, 2019)
Climate change has a negative impact on rice production in Indonesia. This research was conducted to identify problems caused by climate change on agriculture, identify the technology to address climate change, and analyze the technological adaptation to encounter the climate change problems in West Java. Problems arising from climate change include increasing air temperature, rainy season shift, and prolonged drought. The impact of climate change on agricultural land in West Java is prolonged drought and land degradation. The most appropriate technology to be applied in West Java in order to address climate change is System of Rice Intensification (SRI). SRI rice cultivation can save water up to 30% compared to conventional cultivation, so it can be applied when the water resources was limited. SRI method that has been applied in West Java shows that organic rice farming produces more rice than inorganic farming. The productivity of inorganic farming are 6.0 - 7.0 tons / ha, whereas the SRI organic farming could produce 8 - 9.2 tons / ha grain. The application of the SRI method in Cibarengkok Village, Bojong Picung, West Java produces 7-8 tons / ha of grain, while the conventional method yields 4-5 tons / ha of grain.